Penerapan Saluran Pencampur Pada Sistem Irigasi Tambak - Dian Noorvy Khaerudin; Denik Sri Krisnayanti (Balai Teknik Irigasi, 2014)
Indonesia as an agricultural country has a plan in food endurance. Food endurance is also a goal of the MDG 's 2015 Millennium Development Goals were made at Indonesian food resilience into national strategic issues . Indonesia has potential for abundant natural resources , including water resources and fisheries . The types of fish is a source of protein for the body and it plays an important role in improving the nutritional well-being in terms of public health . Brackish water fishery developed are milk fish and shrimp . Sidoarjo district has a regional commodity and smoked milkfish. So most people in Sidoarjo district has these fisheries . But more and more reduced because in addition to its water quality is not maintained as well as irrigation systems are still not organized . The irrigation system is important because with this system of distribution of water activities , prepare pattern of planting , fertilization fish , enlargement , to marketing can work well . Mixer Channel brackish water is a mixture of fresh water and sea water with the required water quality. The problem tertiary channels that directly relate to the primary channel , and can not provide the required water quality ponds . The purpose of making the mixer channel are application the mixer channel for water quality of salinity that available for fish pond and addressing water quality problems that affect the productivity of the farm , and run the irrigation system , water distribution , so organized and structured . And mixer channel with sluice gate will be effective as to split water bearer channel to channel tertiary pond .